Vascular complications in type 2 diabetes mellitus patients and their association with hypertension and dyslipidemia - Khalid, Mohd Khairul Ashraf (2018)
Background: Type 2 diabetes mellitus (T2DM) is a common non communicable disease among population of Marang district. T2DM is a chronic disease which may progress to vascular complications. Hypertension and dyslipidemia are two common co morbidities in T2DM. Objective: This study aimed to study the occurence of vascular complications and their asscoiated factors among T2DM patients in Marang from 2010 to 2016. Methodology: This is a cross sectional design using secondary data of registered T2DM patients from January 2010 to December 2016 in National Diabetic Registry (NDR) database, Non Communicable Disease Unit, District Health Office Marang, Terengganu. All registered T2DM cases with no missing data variable were included For trend analysis, and 500 samples were randomly selected to describe the type of vascular complication and determine the association between hypertension and dyslipidemia with vascular complication. Result: Six thousand four hundred and eighty seven T2DM cases had been registered in NDR Marang from 2010 to 2016. The T2DM patient‘s age ranged from 23 to 93 years old. There were more female 362(72.4%) as compared to male patients 138(27.6%). Majority of the T2DM patients were Malay 478(95.6%). Majority of the patients were overweight group (BMI ≥25kg/m²) 185(37%). The mean HbA1c of the T2DM patients was 8.6(2.29). Majority, 431(86.2%) of the T2DM patients did not achieve good glycaemic control target of HbA1c less than 6.3% . Hypertension present in 340(68%) whereas 357(71.4%) has dyslipidaemia. One hundred and eighteen(23%) had vascular complications,either nephropathy, retinopathy, ischemic heart disease (IHD), cerebrovascular disease, diabetic foot ulcer and amputations as single or multiple complications. The most common vascular complications was nephropathy 59(11.8%) followed by retinopathy 47(9.6%). The highest detection of nephropathy were 116 in 2010 which then fluctuate before reducing back in 2016. Retinopathy complication remained high since the year 2010 to 2016. The highest case of retinopathy detected were 91 case in 2015 and the lowest detected were 61 case in 2013. IHD reducing from 2010 to 2013 but increase steadily again by 2014. Diabetic foot ulcer, amputation and cerebro vascular disease remain at lower frequency through out 2010 to 2016. Presence of hypertension(AdjOR 1.750, 95%CI(1.062, 2.886) p-value 0.028) and dyslipidemia(AdjOR 1.858, 95%CI: 1.092, 3.160; p-value 0.022 ) was found to be significantly associated with the presence of vascular complication Conclusion: Vascular complications especially nephropathy and retinopathy still pose a public health problem among T2DM patients in Marang. Presence of hypertension and dylipidemia increase the risk of vascular complication.